Task ambiguity and academic procrastination: An experience sampling approach. (October 2022) - Wieland, Lena M.; Hoppe, Johannes D.; Wolgast, Anett; Ebner-Priemer, Ulrich W.
Abstract: Procrastination is thought to be affected by trait-based and by situational, or task-specific determinants. Situational and task-specific influences on students' procrastination behavior have rarely been studied. Most research has examined trait-based individual differences in students' general procrastination tendencies. This study used an adaptive experience sampling approach to assess students' ( N = 88) task-related perceptions of ambiguity and their situation-specific procrastination behavior during exam preparation six times a day for seven days ( n = 3581 measurements). Results revealed that 30% of all intended study sessions were procrastinated. The risk that study sessions were procrastinated increased with students' task-related ambiguity perceptions. Individuals' average risk of procrastinating study sessions was further predicted by their procrastination tendency and conscientiousness assessed at baseline. The findings suggest interventions that promote students' ability to self-regulate but also modify tasks and instructions. Further implications and suggestions for future research are discussed. Highlights: Experience sampling of task ambiguity perceptions and procrastination behavior. Captured students' real-life behavior over seven days during exam preparation. Task-specific ambiguity perceptions increase the risk for procrastination behavior. Complementary influence of trait-based and task-specific determinants on behavior. Task characteristics (like ambiguity) should be considered in interventions.